The health impacts of violence perpetrated by police, military and other public security forces on gay, bisexual and other men who have sex with men in El Salvador. Issue 2 (1st February 2020) - Davis, Dirk A.; Morales, Giuliana J.; Ridgeway, Kathleen; Mendizabal, Modesto; Lanham, Michele; Dayton, Robyn; Cooke, Juana; Santi, Karin; Evens, Emily
Abstract: Gay, bisexual and other men who have sex with men face both high levels of violence and a disproportionate burden of poor health outcomes. We explored violence perpetrated against Salvadoran gay, bisexual and other men who have sex with men by public security forces; perceived motivations of violence; and impacts on health. We conducted structured qualitative interviews with 20 participants and used systematic coding and narrative analysis to identify emergent themes. Nearly all participants described the physical, emotional, sexual and/or economic violence by public security forces. Most attributed being targeted to their gender expression and/or perceived sexual orientation. The most common impact was emotional distress, including humiliation, fear and depression; lasting physical injuries were also widely reported. Study participants felt unable to report these incidents for fear of retribution or inaction. Men reported feelings of helplessness and distrust, avoidance of authorities and altering when, where or how often they appeared in public spaces. Programmes and interventions should focus on providing mental health services for LGBTI (lesbian, gay, bisexual, transgender and intersex) victims of violence, educating public security forces on the legal rights of Salvadorans and expanding current LGBTI-inclusive policies to all public security forces.